2020
DOI: 10.5433/1679-0359.2020v41n1p285
|View full text |Cite
|
Sign up to set email alerts
|

Adaptability of sheep to three salinity levels in different environments

Abstract: The objective of this study is to evaluate physiological parameters and the adaptability of Santa Inês sheep to two climatic conditions 25ºC (within the thermal comfort zone [TCZ) and 32ºC (above the TCZ) and three salinity levels (2.0, 4.0, and 8.0 dS m -1 ). The study was developed in a climatic chamber using 36 uncastrated male sheep. The experimental design was completely randomized with a 2 ´ 3 factorial scheme composed of two temperatures, three water salinity levels, and six repetitions. The physiologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 18 publications
0
8
0
1
Order By: Relevance
“…The difficulty in obtaining good-quality water has intensified the demand of saline water for small ruminants to drink (Moura et al, 2016;Mdletshe et al, 2017;Paiva et al, 2017;Albuquerque et al, 2020), which characterizes a recurrent scenario in arid and semiarid regions wherein water may have salt levels above the recommended levels for domestic animals (Manera et al, 2016;Melo et al, 2017). Sheep such as those of the Santa Inês breed have excellent water restriction capability (Silva et al, 2016) and can consume forages that are chemically composed of high salt concentrations (Fahmy et al, 2010;Khanum et al, 2010;Moreno et al, 2015) and water with high salt levels (Yousfi et al, 2016;Castro et al, 2017;Furtado et al, 2020). Araújo et al (2010) showed that sheep could tolerate water with a salinity of up to 8.0 dS m -1 without ingestion, causing harm to the health of the animals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The difficulty in obtaining good-quality water has intensified the demand of saline water for small ruminants to drink (Moura et al, 2016;Mdletshe et al, 2017;Paiva et al, 2017;Albuquerque et al, 2020), which characterizes a recurrent scenario in arid and semiarid regions wherein water may have salt levels above the recommended levels for domestic animals (Manera et al, 2016;Melo et al, 2017). Sheep such as those of the Santa Inês breed have excellent water restriction capability (Silva et al, 2016) and can consume forages that are chemically composed of high salt concentrations (Fahmy et al, 2010;Khanum et al, 2010;Moreno et al, 2015) and water with high salt levels (Yousfi et al, 2016;Castro et al, 2017;Furtado et al, 2020). Araújo et al (2010) showed that sheep could tolerate water with a salinity of up to 8.0 dS m -1 without ingestion, causing harm to the health of the animals.…”
Section: Introductionmentioning
confidence: 99%
“…Factors such as elevation or air temperature can cause behavioral changes in sheep, including reduced feed intake and increased water intake (Torres et al, 2017;Furtado et al, 2020). In addition, the consumption of saline water promotes changes in the efficiency of feeding, rumination, and chewing (Moura et al, 2016), leading to Engenharia Agrícola, Jaboticabal, v.41, n.1, p.19-24, jan./feb.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Moura et al (2016) reported changes in feed efficiency, rumination, and water consumption with the elevation in salinity levels of water offered to sheep. Elevation and air temperature, for example, may induce behavioural changes in sheep, such as decreased feed intake and increased water consumption (Furtado et al 2020).…”
Section: Behavioral Mechanismsmentioning
confidence: 99%
“…The Brazilian Amazon region is characterized by high rainfall, with high temperatures and relative humidity, where sheep are raised in extensive and semi-intensive systems and, in some regions and times of the year, they are confined to the adult stage to improve rates of productive and reproductive (Furtado et al 2017). As a result, Santa Inês sheep and its crossbreeds have a high degree of rusticity and adaptability (Oliveira et al 2015;Pantoja et al 2017;Furtado et al 2020), but as endothermic animals, they depend on ambient temperature to regulate body temperature, with thermal discomfort being one of the factors responsible for their low productivity (Moraes et al 2020).…”
Section: Introductionmentioning
confidence: 99%